Population health post-pandemic: critiquing the economic approach to recovery - Debs Shipton; Gerry McCartney; Robert McMaster (Elsevier, 2021)
The COVID-19 pandemic has exposed that the economic crisis is inseparable from the health and inequalities crisis. This commentary identifies the key overarching economic decisions that governments will make that are likely have a larger impact on the health of nations than the direct impact of COVID-19 itself. We present these economic decisions to a health audience. The public health profession will need to develop opinions on these key economic decisions if we are to shape the environment that has such a large impact on the work we do.